2015
DOI: 10.18632/oncotarget.3615
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule induction of phospho-eIF4E sumoylation and degradation via targeting its phosphorylated serine 209 residue

Abstract: As phospho-eIF4E (p-eIF4E), unlike total eIF4E (t-eIF4E) essential for normal cells, is specifically required by cancer cells, it is an attractive, yet unrealized, target for anti-tumor intervention. Here we identify a small molecule, homoharringtonine (HHT), that antagonizes p-eIF4E function and eradicates acute myeloid leukemia (AML) expressing high level of p-eIF4E in vitro and in vivo. HHT selectively reduces p-eIF4E levels of leukemia cells without affecting t-eIF4E. HHT targets the phosphorylated serine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(37 reference statements)
1
17
1
Order By: Relevance
“…HHT, a traditional Chinese medicine-based agent, has been used for leukemia treatment for more than three decades (5)(6)(7)(8)(9)(10)(11), with well-recognized inhibitory effects on the expression of short-halflife proteins. Recently, more potential HHT target proteins have been reported, suggesting a broader mode of action of the drug (26,27). In this study, we found that HHT inhibited the activity of LICs and improved survival in t(8;21) AML mice.…”
Section: Discussionsupporting
confidence: 52%
“…HHT, a traditional Chinese medicine-based agent, has been used for leukemia treatment for more than three decades (5)(6)(7)(8)(9)(10)(11), with well-recognized inhibitory effects on the expression of short-halflife proteins. Recently, more potential HHT target proteins have been reported, suggesting a broader mode of action of the drug (26,27). In this study, we found that HHT inhibited the activity of LICs and improved survival in t(8;21) AML mice.…”
Section: Discussionsupporting
confidence: 52%
“…As far as we known, HHT has multiple drug targets. Ying Gu et al reported that p-eIF4E was a drug target of HHT [4]. Instead, we found myosin-9 was one of the critical targets in AML cell lines.…”
Section: Introductioncontrasting
confidence: 65%
“…Five best druggable sites of the FEN1 protein were predicted using our in-house developed Druggable Site Prediction (DSP) algorithm (Gu et al, 2015) (Fig. 3b).…”
Section: Resultsmentioning
confidence: 99%